Training in Making Dimsum Made from Jerbung Shrimp as an Effort to Utilize Fishery Potential in Teminabuan District, South Sorong Regency - Lestari, Uun; Dara, Anna; Shyiang Sri, Putri Meira; Ramadani, Soraya; Jasmani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Community service activities that have been carried out are generally based on seeing the potential of fisheries in South Sorong in particular, in Teminabuan District which is quite high. In addition, due to the low level of fishery-based processing, mothers who do not have the knowledge, skills and motivation are the target participants so that they can have a busy life and earn additional income. This service aims to provide training so that they can utilize the potential of fisheries with the method of processing intact raw materials into products that can be sold by utilizing science and technology, so that in the end mothers can help their families. The method used in this service activity is Participatory Learning And Action (PLA), which is a learning technique that emphasizes the learning process together because the learning mechanism is accompanied by the direct application of the dimsum processing process. Through this shrimp processing activity, mothers are able to provide healthy and nutritious intake to the family as well as the first step to bring up ideas and interest in entrepreneurship.